Isolation of adaptive varieties of tomato and innovative technologies for their cultivation on slightly saline soils of the Bukhara region - Toshtemir Еshimovich Оstоnаkulоv; Gulshoda Anvar qizi Sаidоvа; Аnvar Аkbarovich Shаmsiеv (American Journal Of Agriculture And Horticulture Innovations, 2025)
The article presents the results of assessing the collection of tomato hybrid varieties in terms of early maturity, adaptability, formation of the leaf surface, tops, root system and productivity, and as a result, high- yielding, adaptive hybrid varieties and the improvement of the elements of agricultural technology for their cultivation, such as irrigation regimes, fertilizer rates, planting patterns and standing density for slightly saline soils. It was revealed that hybrid varieties of tomato were distinguished - Seraj F1, Tomck F1, Bobcat F1, Lojain F1, which formed tall plants (51.3- 60.2 cm), root weight - 124-144 g, tops - 473-574 g, fruit yield per bush – 1525.5-2470.5 g. These hybrid varieties provided the highest yield (67.8-109.8 t/ha). In the selected adaptive hybrid varieties, the optimal soil moisture regime was not lower than 75-85-85% of the PSMC and the application of fertilizers at the rate of 20 t/ha of manure + N200P160K100 kg/ha. At the same time, the yield of hybrid varieties (48.6-88.1 t/ha), the yield per 1 m3 of water was the highest (5.7-9.8 kg), and the water consumption per 1 centner of the crop was the 2-17.5 m3) and the content of nitrates in fruits did not exceed the recommended norm (44.7-67.8 mg/kg). The optimal planting scheme was 90x25 cm, with a density of 44.4 thousand plants per 1 ha, where it provided a high yield (25.3-90.0 tons).